Rosettes and Pseudorosettes and Their Significance (Journal of Enam Medical College, 2017)
Rosettes are round assemblage of cells found in tumors. They usually consist of cells in a spoke circle, a halo collection surrounding a central or a cellular lumen. Rosettes are so named for their similarity to the rose casement found in gothic cathedrals. There are clusters of different kinds of rosettes in pathology, each with different kind of cells and dissimilar names. Most of them are found in tumors of the nervous system. The detection of rosettes help in diagnosis of different tumors.J Enam Med Col 2017; 7(2): 101-106